Usulan Perencanaan Pemeliharaan Mesin Cetak GTO Menggunakan Metode Reliability Centered Maintenance (RCM) II - Fahir Raudy; Nita P.A Hidayat; Ajrina Febri Suahati (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. PT.Granesia is a company engaged in printing and publishing. The obstacle experienced by PT.Granesia when carrying out the production process is the number of defective products in the form of rejected products. This causes losses to the company in the form of financial and material, to overcome this it is necessary to make improvements to the maintenance of machine components. In this study, the Reliability Centered Maintenance (RCM) II method is used which is a maintenance method. Based on the background that has been described, the objectives in this study are to identify the current maintenance method of the GTO Print machine, design a proposed preventive maintenance schedule that can reduce rejected products and increase reliability on the GTO Print machine, and calculate the preventive costs and failure costs that must be incurred by the company to perform maintenance on the GTO Print machine. In the current condition, the company applies corrective maintenance with reliability for blanket components of 41,401%, bearings of 49,189%, roll air of 50,313%, and bearing housings of 52,121%, resulting in maintenance costs of Rp. 845.968.340. In achieving a reliability level of 80%, maintenance intervals of blanket components are carried out every 28 hours with a reliability of 80,541%, bearings every 132 hours with a reliability of 80,757%, roll water every 228 hours with a reliability of 80,301%, and bearing housings every 174 hours with a reliability of 80,487%. Based on the results of the maintenance interval, five scenarios were then carried out, from the existing scenarios, scenario two was selected, namely separate maintenance outside company working hours for blanket components every 28 hours, bearings every 133 hours, roll water every 223 hours, and bearing housings every 174 hours at a cost of Rp.165.192.533. Abstrak. PT.Granesia merupakan perusahaan yang bergerak di bidang percetakan dan penerbitan. Kendala yang dialami PT.Granesia ketika melakukan proses produksi yaitu banyaknya produk cacat yang berupa rejected product. Hal tersebut menyebabkan kerugian bagi perusahaan berupa finansial maupun material, untuk mengatasi hal tersebut perlu dilakukan perbaikan dengan perawatan komponen mesin. Dalam penelitian ini digunakan metode Reliability Centered Maintenance (RCM) II yang merupakan metode pemeliharaan. Berdasarkan latar belakang yang telah diuraikan, maka tujuan dalam penelitian ini adalah mengidentifikasi metode pemeliharaan mesin Cetak GTO saat ini, mendesain usulan jadwal preventive maintenance yang dapat mereduksi rejected product dan meningkatkan keandalan pada mesin Cetak GTO, serta menghitung biaya preventive dan biaya failure yang harus dikeluarkan perusahaan untuk melakukan pemeliharaan pada mesin Cetak GTO. Pada kondisi saat ini, perusahaan menerapkan corrective maintenance dengan keandalan untuk komponen blanket sebesar 41,401%, bearing sebesar 49,189%, roll air sebesar 50,313%, dan rumah bearing sebesar 52,121%, sehingga diperoleh biaya pemeliharaan sebesar Rp. 845.968.340. Dalam mencapai tingkat keandalan 80%, dilakukan interval pemeliharaan komponen blanket setiap 28 jam dengan keandalan sebesar 80,541%, bearing setiap 132 jam dengan keandalan 80,757%, roll air setiap 228 jam dengan keandalan 80,301%, dan rumah bearing setiap 174 jam dengan keandalan sebesar 80,487%. Berdasarkan hasil interval pemeliharaan kemudian dilakukan lima skenario, dari skenario yang ada, terpilih skenario dua yaitu pemeliharaan terpisah di luar jam kerja perusahaan untuk komponen blanket setiap 28 jam, bearing setiap 133 jam, roll air setiap 223 jam, dan rumah bearing setiap 174 jam dengan biaya sebesar Rp.165.192.533.